The Effect of Chronic Disease Management Program to Hiperkolesterol Diseases at Indonesian Worker he Companies - Rian Nurahman; Suhat; Novie Muliku; Dyan Kunthi N (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: Hypercholesterol is an increase in cholesterol levels in the blood that exceeds normal limits. Based on MCU employees result in 2022, there were 288 people suffering from hypercholesterol, out of 591 total HE employees. The Chronic Disease Management Program (CDMP) intervention is one of the efforts used to overcome this disease. Objective: The aim of this study was to determine the effect of CDMP on reducing high total cholesterol levels in offshore workers at Indonesian HE’s companies. Method: The research design used a quasi experiment, pretest-posttest with control group design. The population is offshore workers who suffer from hyperchoelsterol. the sample size is 30 people in each group. Dependent variable is total cholesterol levels and the independent variables CDMP that are aerobic exercise, diet planning and health education. The sampling technique uses purposive sampling. The statistical analysis used was univariate and bivariate, with paired sample T-Test and independent sample T-test, and to measure the effectiveness of the program, it is determined based on the N-Gain Percent. Result: The results of the study showed differences in total cholesterol levels before and after the CDMP intervention in the intervention group (p-value=0.000) and the control group (p-value=0.000). The results of different test after CDMP intervention between both groups showed (p-value=0.000), The N-Gain score for the intervention group was 71% and for the control group was 40%, so the effectiveness of CDMP intervention on reducing total cholesterol by by 31%. Conclusion: The CDMP intervention was quite effective in reducing total cholesterol levels in the intervention group compared to the control group by 31%. It is recommended for hypercholesterol’s person to carry out CDMP intervention through controlling aerobic exercise, diet planning, and regular health education.